Determinants for the innovation activities in Malaysia and selected countries - Yap, Jia Ru (2024)
This study delves into the determinants of innovation activities in Malaysia, the United States, China, South Korea, and Singapore, with a specific focus on Research and Development (R&D) expenditure as a percentage of Gross Domestic Product (GDP). Innovation plays a crucial role in driving economic growth, societal progress, and global competitiveness, making it imperative to understand the factors that influence innovation landscapes across diverse national contexts.